Association between interleukin-2 (rs2069762) gene polymorphism and FVIII inhibitor development in Indonesian patients with severe hemophilia A (Faculty of Medicine Universitas Indonesia, 2022)
BACKGROUND Factor VIII (FVIII) inhibitors in hemophilia A (HA) patients render FVIII replacement therapy ineffective. Although its development cause is unclear, it has been classified into therapeutic and genetic-related etiologies. Single nucleotide polymorphisms (SNPs) in several cytokine genes, including interleukin (IL)-2, could increase the risk of FVIII inhibitor development. This study aimed to evaluate the association between IL-2 (rs2069762) gene SNP and FVIII inhibitor development in Indonesian patients with severe HA. METHODS The IL-2 (rs2069762) gene SNP was examined in 119 HA patients. The presence of FVIII inhibitors was quantified using an enzyme-linked immunosorbent assay, with a titer of <0.28 ng/ml considered negative. Patients were divided into two groups: 59 with FVIII inhibitors (positive group) and 60 without inhibitors (negative group). The genotype of the subjects was determined using peripheral blood mononuclear cells and tetra-primer amplification refractory mutation system-polymerase chain reaction. RESULTS There was no association between IL-2 (rs2069762) gene polymorphism and FVIII inhibitor development on genotypes (p = 0.138) and allele frequencies (p = 0.780). CONCLUSIONS IL-2 (rs2069762) gene polymorphism is not a risk factor in the development of FVIII inhibitors in Indonesian patients with severe HA. Thus, further polymorphism studies in other cytokine genes are required to gain a comprehensive understanding of the FVIII inhibitor development.